Handling Child Victims of Criminal Sexual Violence in Jeneponto Regency, South Sulawesi Province - J, Sunarti; Lahaling, Hijrah; Darmawati, Darmawati (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
Handling of children's cases in Indonesia is based on the Regulation of the Minister of State for Women's Empowerment and Child Protection concerning Guidelines for Handling Child Victims of Violence. Sexual violence committed against minors will of course have an impact on the psychological aspects and other development of the child. This research aims to determine the treatment of child victims of criminal acts of sexual violence that has been implemented in Jeneponto Regency, South Sulawesi Province, research that examines empirical juridical . Which reviews the existence of sexual violence committed against children. Data collection was carried out using interview techniques. So we need a way to ensure that acts of violence against children do not continue to be carried out and firm action must be taken by the government who commits violence. So it is deemed necessary to confirm the regulations that have been implemented by the government, especially Law Number 23 of 2002 concerning child protection.